Potensi Produk Organik Kabupaten Lumajang: Studi Komoditas Kopi Robusta - Soejono, Djoko; Arum, Ayu Puspita; Utami, Ratih Apri; Romadhona, Sukron (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Utilization and development of plantation sector production results, one of which is robusta coffee commodities. Lumajang District with a production of 7.83% of the total coffee production in East Java Province. This study aims to determine the mapping of potential, application of agribusiness systems, economic value, and strategies for developing organic products of robusta coffee commodities in Lumajang District. The research location was selected purposively in the Lumajang District area. The sampling method is by purposive sampling and snowball sampling. The data collection method used in this study uses observation, interview, and Focus Group Discussion (FGD) techniques. The data sources in this study are primary and secondary data. The results of the study indicate that the development of organic robusta coffee is very suitable in the Candipuro, Pasrujambe, Pronojiwo, Ranuyoso and Senduro Districts. The application of the agribusiness system is carried out through intercropping with other commodities. The obstacles experienced are: the quality of the cuttings from the garden is not guaranteed, the materials for making fertilizers and pesticides are not guaranteed to be free from chemical contamination, cultivation, harvesting and post-harvest equipment is used for inorganic activities, and there are no supporting facilities for the wet processing process, limited labor in terms of quantity and quality (skills), access to capital sources is still limited, the market for organic coffee products is limited because there has been no formal partnership and weak institutional management of farmer groups or Gapoktan. The results of economic calculations of organic robusta coffee products can reduce production costs by up to 20%. The priority choice of organic robusta coffee product development strategies is the importance of strengthening farmer institutions in the form of Farmer-Owned Enterprises (BUMP) in order to increase the entrepreneurial spirit, while strengthening the bargaining position in the organic product market mechanism based on science and technology.